A new perspective for understanding the contributions of the cerebellum to reading: The cerebro-cerebellar mapping hypothesis. (6th June 2022) - Li, Hehui; Yuan, Qiming; Luo, Yue-Jia; Tao, Wuhai
Abstract: Extensive studies have reported significant activation of the cerebellum in reading and reading-related tasks. However, it has remained unclear how the cerebellum contributes to reading and how reading-related regions in the cerebrum are related to those in the cerebellum. In this review, by summarizing previous literature, we observe that multiple cerebellar areas are engaged in reading and vary in their contributions to reading. Moreover, the cerebellar reading-related areas are selectively connected with the cerebral areas with the same functional specificity. Abnormalities in the cerebro-cerebellar connection are also associated with reading impairments. We thus propose the cerebro-cerebellar mapping hypothesis, which suggests that the cerebellum might have another reading-related network rather than serving as a neural hub. This network maps to and collaborates with its functionally corresponding network in the cerebrum. This framework heightens the importance of the cerebellum to reading and provides new insights into the relationship between the cerebellum, cerebrum, and reading development. Highlights: We proposed the cerebro-cerebellar mapping hypothesis for word reading. This framework claimed that the cerebellum has multiple reading-related areas, mapping to those in the cerebrum. Fluent reading requires the collaboration of the cerebral and cerebellar reading-related areas. Dysfunction of the cerebro-cerebellar connection was associated with reading impairments.